Role of activating transcription factor 3 protein ATF3 in necrosis and apoptosis induced by 5‐fluoro‐2′‐deoxyuridine. (6th March 2014) - Sato, Akira; Nakama, Kentaro; Watanabe, Hiroki; Satake, Akito; Yamamoto, Akihiro; Omi, Takuya; Hiramoto, Akiko; Masutani, Mitsuko; Wataya, Yusuke; Kim, Hye‐Sook
<x xml:space="preserve">Abstract</x> Necrosis and apoptosis are the two major forms of cell death. We have studied the mechanisms that regulate the cell death observed during treatment of mouse cancer cell line FM3A with the anticancer drug 5‐fluoro‐2′‐deoxyuridine (FUdR). To detect causal differences between necrosis and apoptosis, we exploited the necrosis in original clone F28‐7 and the apoptosis in its variant F28‐7‐A that occur on treatment with FUdR. Activating transcription factor 3 (ATF3) was strongly induced during necrosis but not apoptosis. In addition, we found that ATF3 expression is regulated by heat shock protein 90 (HSP90) at the mRNA stage. Knockdown of Atf3 by siRNA in the F28‐7 cells resulted in apoptotic morphology rather than necrotic morphology. These results suggest that ATF3 is a cell‐death regulator in necrosis and apoptosis.